Find the values of a and b so that \( \lim_{x \to 0} \frac{x(1 - a \cos x) + b \sin x}{x^3} = \frac{1}{3} \).
![Question image](https://assets.quizgecko.com/question_images/R43UTk3863YRJKgiUqgX2SzFdW6gpndX7qd9tuRG.jpg)
Understand the Problem
The question is asking for the values of the variables 'a' and 'b' so that the given limit, as x approaches 0, exists and is equal to 1/3.
Answer
The values are \( a = \frac{1}{2} \) and \( b = -\frac{1}{2} \).
Answer for screen readers
The values of ( a ) and ( b ) are: $$ a = \frac{1}{2}, \quad b = -\frac{1}{2} $$
Steps to Solve
- Expand the Functions To solve this limit, we need to expand ( 1 - a \cos x ) and ( b \sin x ) using Taylor series around ( x = 0 ):
- The expansion of ( \cos x ) is ( 1 - \frac{x^2}{2} + O(x^4) )
- The expansion of ( \sin x ) is ( x - \frac{x^3}{6} + O(x^5) )
Thus, we have: $$ 1 - a \cos x \approx 1 - a \left(1 - \frac{x^2}{2}\right) = 1 - a + \frac{ax^2}{2} $$
And: $$ b \sin x \approx b \left(x - \frac{x^3}{6}\right) = bx - \frac{bx^3}{6} $$
- Combine the Expanded Terms Now, substituting back into the limit expression, we can combine: $$ x(1 - a \cos x) + b \sin x \approx x(1 - a + \frac{ax^2}{2}) + bx - \frac{bx^3}{6} $$
This becomes: $$ (1 - a + b)x + \frac{ax^3}{2} - \frac{bx^3}{6} $$
- Form the Expression for the Limit Now we formulate the limit as: $$ \lim_{x \to 0} \frac{(1 - a + b)x + \left(\frac{a}{2} - \frac{b}{6}\right)x^3}{x^3} $$
Separating the terms gives us: $$ \lim_{x \to 0} \left(\frac{(1 - a + b)}{x^2} + \left(\frac{a}{2} - \frac{b}{6}\right)\right) $$
-
Setting the Conditions for the Limit to Exist For the limit to exist, the term involving ( x^2 ) must vanish, so we set: $$ 1 - a + b = 0 \implies b = a - 1 $$
-
Solving for ( a ) and ( b ) We need the constant term to equal ( \frac{1}{3} ): $$ \frac{a}{2} - \frac{(a - 1)}{6} = \frac{1}{3} $$
Converting and combining gives: $$ \frac{3a - (a - 1)}{6} = \frac{1}{3} $$ $$ \frac{2a + 1}{6} = \frac{1}{3} $$ $$ 2a + 1 = 2 \implies 2a = 1 \implies a = \frac{1}{2} $$
Substituting back gives: $$ b = \frac{1}{2} - 1 = -\frac{1}{2} $$
The values of ( a ) and ( b ) are: $$ a = \frac{1}{2}, \quad b = -\frac{1}{2} $$
More Information
This result tells us that for the limit to exist and equal ( \frac{1}{3} ), the coefficients ( a ) and ( b ) must be set to these specific values. This demonstrates the balance needed in Taylor expansions when analyzing limits.
Tips
When solving limits involving Taylor series, a common mistake is to neglect to include higher order terms, leading to incorrect results. Always ensure to keep track of all relevant terms in the expansions.
AI-generated content may contain errors. Please verify critical information